2015
DOI: 10.1002/mds.26485
|View full text |Cite
|
Sign up to set email alerts
|

Integrated safety of levodopa‐carbidopa intestinal gel from prospective clinical trials

Abstract: BackgroundContinuous administration of levodopa‐carbidopa intestinal gel (carbidopa‐levodopa enteral suspension) through a percutaneous endoscopic gastrojejunostomy is a treatment option for advanced Parkinson disease (PD) patients with motor fluctuations resistant to standard oral medications. Safety data from 4 prospective studies were integrated to assess the safety of this therapy.MethodsSafety data from 4 studies were summarized using 2 overlapping data sets, permitting the separation of procedure/device–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
69
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 38 publications
(87 reference statements)
17
69
3
2
Order By: Relevance
“…Results from this prospective, multicenter, observational study showed significant improvements in activities of daily living, motor and non-motor symptoms, and quality-of-life scores, with safety results in accord with the known safety profile of LCIG [11, 12, 17]. These results extend current findings, which have focused primarily on the effect of LCIG on motor complications [1012, 14].…”
Section: Discussionsupporting
confidence: 81%
“…Results from this prospective, multicenter, observational study showed significant improvements in activities of daily living, motor and non-motor symptoms, and quality-of-life scores, with safety results in accord with the known safety profile of LCIG [11, 12, 17]. These results extend current findings, which have focused primarily on the effect of LCIG on motor complications [1012, 14].…”
Section: Discussionsupporting
confidence: 81%
“…The majority of our patients were satisfied with the infusion during follow‐up. There were, however, numerous tube and stoma complications related to LCIG, as reported previously (Fernandez et al., ; Lang et al., ; Nilsson et al., ).…”
Section: Discussionsupporting
confidence: 74%
“…Complications with the PEG‐J tube (Devos, ; Fernandez et al., ; Nyholm et al., ) are similar to complications related to PEG for feeding purposes (Schapiro & Edmundowicz, ; Udd et al., ). The risk of peritonitis has varied between zero and 4% (Devos, ; Epstein et al., ; Lang et al., ; Palhagen et al., ), and other serious complications like colonic perforations, gastropleural fistula (Klostermann et al., ) and liver injury (Pickut et al., ), have also been described. In our material, we did not have any peritonitis, nor any need for emergency abdominal surgery due to LCIG complications.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may experience increasing dyskinesias,64 but optimized LCIG infusion may also be used to treat troublesome dyskinesias 65. Safety data from four prospective studies were recently integrated to assess the safety of LCIG infusion after median 911‐day treatment 66. The most frequently reported procedure/device adverse events were complications of device insertion and abdominal pain, considered serious in 17% of the patients.…”
Section: Device‐aided Treatment Optionsmentioning
confidence: 99%